Knowledge, attitude and practice of over the counter (OTC) drugs among undergraduate students of International Islamic University Malaysia (IIUM) Kuantan, Pahang - Abd Hamid, Abdul Alif; Roseli, Nurul Nadzirah; Nurumal, Mohd Said; Abd Hamid, Hamizah (Community Practitioner, 2023)
Introduction: It is human’s nature to seek for immediate relief when they are feeling sick thus,many choose to self-medicate. Self-medication drugs are frequently referred to as 'non- prescription’ or over the counter (OTC) drugs since they can be acquired without a prescriptionfrom pharmacies and some non-pharmacy store outlets. It was proven to be common among students who are enrolled in health- related courses which driven by many factors. Objective: The objective of this study is to determine the level of knowledge, attitude, and practice towards OTC drugs among undergraduate students at International Islamic University Malaysia (IIUM)Kuantan and its association with the sociodemographic data. Methodology: A quantitative cross-sectional study with simple random sampling study was conducted among 245 undergraduate students of IIUM Kuantan Campus, from May to June 2022. Data was collectedby using Google Forms questionnaires which available in English language and distributed toall the students online. Two set of questionnaires were adapted and adopted from previous studies Data was analysed by using SPSS version 28.0. Results: The study showed that most participants had a good knowledge level (49.8 %) and a positive attitude towards OTC drugs (53.9%) but had poor OTC drug practice (56.7 %). This study also reported significant associations between Kulliyyah and the year of study factors with knowledge levels on OTC drugs (p < 0.05). Conclusion: In conclusion, the study found that nearly half of the IIUM undergraduate students had good KAP levels towards OTC drugs. However, a sizable portionof them still had low KAP levels for OTC drugs. Hence, the study established preliminary dataon lack of awareness of OTC drugs among undergraduate students at IIUM and the need for the health authority to address the OTC drugs awareness issues starting from the students themselves. Therefore, the results can be used by the health authority to initiate better educationefforts about OTC medications among undergraduate students and staff, which will enable prevention and control actions to be taken in the future.